Penerapan positif dan negatif untuk meningkatkan kedisiplinan siswa SMP Lentera Harapan Lampung Tengah dalam Mapel IPS - Jossapat Hendra Prijanto; Agnes Jumarta Gulo (Universitas Negeri Malang, 2018)
Discipline is an important aspect that every student should have, to achieve the learning objectives. Discipline, however, is often found as a problem in the classroom. This problem was found in grade VIII SMP Lentera Harapan Lampung Tengah students in Integrated IPS subjects. To solve the problem, in this research applied reward and punish to improve student discipline of class VIII. The reward form applied is in the form of praise, tape reward, and sign strengthening (certificate), while the punish form is the cutting of time and cost to be paid, with modifications called 'red box'. The methodology used in this research is Classroom Action Research method. The subjects of the study were students of class VIII with a total of 14 people, consisting of 11 men and 3 women. The results of the study on student discipline levels obtained from this study is the first cycle 69.8%, 83.4% and third cycle 93.8%. It can be concluded that the application of reward and punish can improve the discipline in Integrated Social Science subjects in the seventh grade students of SMP Lentera Harapan Lampung Tengah.DOI: 10.17977/um022v3i12018p053